Solving Zika virus model with vector control using Caputo fractional derivatives. - Meena, Vinita; Agarwal, Vandana (Discover Public Health, 2026)
Globally, the introduction and spread of vector-borne illnesses present serious threats to public health, particularly in areas where the Aedes aegypti mosquito, the disease's main vector, is prevalent. To this end, we investigate novel fractional Zika virus model with Caputo fractional derivative. The fractional formulation captures memory and hereditary effects, providing a more realistic description of biological processes compared with classical integer-order models. The fundamental properties of the model are established, including positivity, boundedness, equilibrium points, and the basic reproduction number. The fractional model has been graphically simulated using MATLAB R2021a. It provides a comprehensive understanding of Zika virus dynamics and assessing vector control strategies.